2022
DOI: 10.1111/jcmm.17322
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate inhibits aerobic glycolysis of hepatocellular carcinoma cells via the c‐myc/hexokinase 2 pathway

Abstract: Aerobic glycolysis is a well-known hallmark of hepatocellular carcinoma (HCC). Hence, targeting the key enzymes of this pathway is considered a novel approach to HCC treatment. The effects of sodium butyrate (NaBu), a sodium salt of the short-chain fatty acid butyrate, on aerobic glycolysis in HCC cells and the underlying mechanism are unknown. In the present study, data obtained from cell lines with mouse xenograft model revealed that NaBu inhibited aerobic glycolysis in the HCC cells in vivo and in vitro. Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Pericyte-hexokinase 2 (HK2) is the key rate-limiting enzyme of the glycolytic pathway, which is associated with pathological stage and prognosis ( DeWaal et al, 2018 ). In the mouse model of HCC, HK2 silencing could synergistically enhance the sensitivity of HCC cells to sorafenib ( Yu et al, 2022 ). CYP26 enzymes are the major enzymes responsible for the clearance of retinoic acid (RA), which is an important endogenous signaling molecule that regulates the cell cycle and maintains epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Pericyte-hexokinase 2 (HK2) is the key rate-limiting enzyme of the glycolytic pathway, which is associated with pathological stage and prognosis ( DeWaal et al, 2018 ). In the mouse model of HCC, HK2 silencing could synergistically enhance the sensitivity of HCC cells to sorafenib ( Yu et al, 2022 ). CYP26 enzymes are the major enzymes responsible for the clearance of retinoic acid (RA), which is an important endogenous signaling molecule that regulates the cell cycle and maintains epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a fifth hexokinase, hexokinase domain containing 1 (HKDC1), was shown to have significant overexpression in liver cancer compared to healthy liver tissue 26 . Studies revealed that inhibiting HK2-mediated glycolysis can enhance the anti-hepatocellular carcinoma activity of sorafenib 27 , 28 . HK2 may be a possible therapeutic target for liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…MACC1 and STAT3 also enhance glucose metabolism and lactate production through HK2 (41,42). Blockade of FOXK1, EGFR, C-MYC signaling inhibits HK2-mediated glycolysis (42)(43)(44). Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) has been considered as a stably expressed reference gene in the past, and GAPDH has been reported to be up-regulated in various cancers (45).…”
Section: Metabolic Reprogramming Promotes Lactate Production In Hccmentioning
confidence: 99%